CHARACTERISTICS OF MECHANICALLY FRACTIONATED AGGREGATES OF TWO CONTRASTING SOILS - Ita Yulnafatmaawita (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
Tillage often decreases physical condition of agricultural land, especially aggregate degradation which causes land and environmental quality decreased. As aggregates disperse into single particles, chemical properties of the soil could change. The objective of this research was to study whether or not mechanical fractionation causes soil dispersion indicating by different chemical properties. Aggregates of two soils, Vertisol and Oxisol, were degraded by using puddler at 3 different energy rates (40, 60, and 150 J kg-1 soil minute-1) and then were separated into 3 different sizes (2000-20, 20-2, <2 um). Therefore, each soil sample would have 15 soil separates at different energy and aggregate size. The result showed that aggregate fractionation especially the fraction size, in general, affected EC, ESP, and CEC but not pH of both soils. The pattern of EC and CEC values seemed to be equal, the highest values were found at the smallest aggregate size (< 2 um). The CEC values of Oxisols did not affected by fractionation, while CEC values of Vertisols increased by decreasing aggregate size, and decreased by increasing energy applied. This indicated that Vertisol is easier to disperse than Oxisol.